2012
DOI: 10.12659/msm.882196
|View full text |Cite
|
Sign up to set email alerts
|

18alpha-Glycyrrhizin induces apoptosis and suppresses activation of rat hepatic stellate cells

Abstract: SummaryBackgroundTo investigate the potential mechanisms underlying the protective effects of 18α Glycyrrhizin (GL) on rat hepatic stellate cells (HSCs) and hepatocytes in vivo and in vitro.Material/MethodsSprague-Dawley (SD) rats were randomly divided into 5 groups: normal control group, liver fibrosis group, high-dose 18α GL group (25 mg/kg/d), intermediate-dose 18α GL group (12.5 mg/kg/d) and low-dose 18α GL group (6.25 mg/kg/d). The rat liver fibrosis model was induced by carbon tetrachloride (CCl4). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…The mitochondrial pathway of apoptosis is regulated by members of the Bcl-2 family, such as Bcl-2, Bcl-xL, and Bax (Qu et al, 2012). Novo et al have demonstrated that activated HSCs are resistant to most proapoptotic stimuli due to Bcl-2 overexpression, which may play a key role in the progression of fibrosis in chronic liver diseases (Novo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial pathway of apoptosis is regulated by members of the Bcl-2 family, such as Bcl-2, Bcl-xL, and Bax (Qu et al, 2012). Novo et al have demonstrated that activated HSCs are resistant to most proapoptotic stimuli due to Bcl-2 overexpression, which may play a key role in the progression of fibrosis in chronic liver diseases (Novo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although liver fibrosis is not malignant in and of itself, the process can destroy normal tissue structure and function and can gradually develop into cirrhosis, and eventually liver cancer. Hepatic stellate cells (HSCs) are vitamin A-storing pericytes found in the space of Disse [ 5 ]. Activation and proliferation of HSCs is pivotal to the development of liver fibrosis [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…18-β GL shows an antiviral activity against a great deal of DNA and RNA viruses due to potential activation of NF-κB and induction of IL-8 secretion [35]. 18-α GL is also reported to suppress the activation of HSCs and induce the apoptosis of HSCs by blocking the translocation of NF-κB to the nucleus [36]. However, abundant basic and clinical studies are still needed to further clarify pharmacological effects of GL, before it's included in the treatment of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%